(3GdfcJ TQM GdLGeY GdcHjQs - (3eMeO Hf CMeO Hf Sgd GdSQNSi GdMfajs; (3eMeO Hf GdMSf GdTjHGfj GdMfaj,J (B187 (3g` s
(3ChdgG (B:s
(3HGH WdGb GdSfI GdPi HGdhcGdI s
(3BNQgG (B:s
(3jLH HGdEdJRGe HGdJJGHY ai GdUhe hYHGQGJfG GdePchQI ai RjGOI GdRjGOGJ s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B568s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdMfajs